(3GdebJQH aj MhGOK GdMVQ hGdYQHs - (3aJM Gddg Hf CfWhf Hf GdUGFZs
(3ChdgG (B:s
(3HSe Gddg GdMi GdfGWb GdCRdi hHg fSJYjf s
(3fSNI ahJZQGa Yf eNWhWI HGQjS GdJi HNW GdeDda JcQQJ CjkVG JMJ Qbe (B" 824" (3JGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B770 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B258 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs